Comparative study of the pharmacokinetics, efficacy and safety of ET-26 in elderly and non-elderly subjects: the results of a phase I clinical trial - Yang, Fan; Sun, Jing; Ye, Pan-Pan; Lv, Wen-Shuo; Li, Li-Ze; Zhao, Bao-Zhong; Van Den Anker, John; Zheng, Yi; Ke, Bo-Wen; Yang, Xiao-Ran; Zhao, Wei (Frontiers in Pharmacology, 2025)
AimTo evaluate the pharmacokinetics, pharmacodynamics, and safety of the novel systemic intravenous anesthetic ET-26—an etomidate derivative designed to reduce adrenal suppression—in healthy elderly and non-elderly subjects.MethodsIn this Phase I, single-center, non-randomized, open-label trial, 16 volunteers were enrolled: eight elderly (≥65 years, including ≥75 years) and eight non-elderly (18–64 years), matched for gender and body weight. Each received a standardized IV infusion of ET-26. Plasma concentrations were measured for plasma protein binding, Cmax, and AUC; time to loss of consciousness (LOC) and safety were assessed.ResultsIn 16 subjects (8 elderly/8 non-elderly), ET-26 showed higher exposure in the elderly (Cmax GMR 198.81%, 90% CI 126.51–312.45) and AUC0−∞ was 23.5% higher (90% CI: 107.6%–141.9%) with comparable pharmacodynamics (median LOC time 1.933 min). Plasma protein binding remained stable (intergroup difference ≤1.0%). Drug-related TEAEs (37.5%) were mild and self-limiting.ConclusionDespite elevated systemic exposure in elderly subjects, ET-26 demonstrates comparable efficacy and retains a favorable tolerability profile across age groups, eliminating the need for dose adjustments in elderly populations.Clinical Trial Registrationhttp://www.chinadrugtrials.org.cn/clinicaltrials.searchlist.dhtml?keywords=CTR20233784, identifier CTR20233784.